2023
DOI: 10.1038/s41598-023-37574-3
|View full text |Cite
|
Sign up to set email alerts
|

Automatic identification of medically important mosquitoes using embedded learning approach-based image-retrieval system

Abstract: Mosquito-borne diseases such as dengue fever and malaria are the top 10 leading causes of death in low-income countries. Control measure for the mosquito population plays an essential role in the fight against the disease. Currently, several intervention strategies; chemical-, biological-, mechanical- and environmental methods remain under development and need further improvement in their effectiveness. Although, a conventional entomological surveillance, required a microscope and taxonomic key for identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 63 publications
1
3
0
Order By: Relevance
“…Additionally, the requirement for fine-tuning in the CBIR protocol may arise, considering that the number of returned images influences the evaluation metrics [ 43 , 50 ]. Although the kNN value of 10 resulted in the average AUC reaching its peak when comparing to the other values [ 20 ], it is noteworthy that employing kNN = 20 in our study yielded comparable results to those reported by Kittichai et al [ 44 ] and represent a soft-voting approach. Nevertheless, it is important to overcome a significant limitation in the CBIR work must be overcome.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Additionally, the requirement for fine-tuning in the CBIR protocol may arise, considering that the number of returned images influences the evaluation metrics [ 43 , 50 ]. Although the kNN value of 10 resulted in the average AUC reaching its peak when comparing to the other values [ 20 ], it is noteworthy that employing kNN = 20 in our study yielded comparable results to those reported by Kittichai et al [ 44 ] and represent a soft-voting approach. Nevertheless, it is important to overcome a significant limitation in the CBIR work must be overcome.…”
Section: Discussionsupporting
confidence: 78%
“…The utilization of DML in automatically identifying Trypanosoma species yields findings line with prior research. One such study employed DML to distinguish between mosquito vector species in Thailand [ 44 ]. Another investigation focused on classifying lung nodules, employing a two-step content-based image retrieval approach that utilized texture features and a learned distance metric [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Models based on insect morphology imaging of immobilized insects, an approach close to the entomological expertise deployed to identify insects that have inter-genus inter-species high morphological similarities, require a considerable number of data for training each Genus/species to learn the features and gain validation accuracy 10 , 13 , 14 . Databases needed to train such models on whole insect recognition are filled with pictures of several poses, dorsal–ventral, etc., to collect taxonomic discrimant characters 6 , 15 17 .…”
Section: Introductionmentioning
confidence: 99%